A construção do corpo na mídia semanal - Silva, Simone Bueno da (2007)
This researche has as objetive to analyze the sense production in the construction of the body in the Brazilian printed media and what these representations tell us about the construction of the contemporary subject's identity. The theoretical and methodological apparatus is based on researches of the discursive semiotics, developed by A. J. Greimas and their collaborators, in the School of High Studies in Paris, mainly on Socio-semiotics proposed by E. Landowski, besides the propositions on plastic semiotics of J-M. Floch, and the studies of A. C Oliveira on fashion and construction of the identity. It takes for object the images of bodies that has been reproduced in the covering of the main magazines of weekly information, including only reportings not attached at a specific time, in the period limited from January 2000 to December 2006. According to circulation order, they are: Veja magazine, of the Abril publisher, Época magazine, of the Globo publisher and Istoé magazine, of the Três publisher. The choice of these magazines took into account the fact of they be destined for a general interest public, once the simulacres of bodies studied are not specifically masculine or feminine, but simulacres that we intend to denominate social. The observation of the thematic and figurative reiterations, guided by invariables and variables elements, led us to the observation of two main discursive isotopies health and body aesthetic on which are organized our discursive analyze. Since then, we have observed bodies simulacres that refer to a subject presence way predominantly subjective and objective. Based on these presence ways, we propose a typology of the simulacres of the body in correlation with different ways of visibility and interaction. The analysis of the enunciation mechanisms in correlation with the way of construction of sense and interaction took us to observation of the way as media operate in the communication on the body, promoting the popularization and maintenance of values related to different manners of the subject to link with his body. Such values, once crystallized, tend to manipulate the body perception that envolves the identity construction process of the contemporary subject, showing the importance of the approach of the mechanisms of sense production in the media, that stands out between those of larger inclusion and effectiveness in the contemporary society